Biodiversity-productivity relationships are key to nature-based climate solutions - Mori, Akira; Dee, Laura; Gonzalez, Andrew; Ohashi, Haruka; Cowles, Jane; Wright, Alexandra; Loreau, Michel; Hautier, Yann; Newbold, Tim; Reich, Peter; Matsui, Tetsuya; Takeuchi, Wataru; et al. (Dryad, 2021)
The global impacts of biodiversity loss and climate change are interlinked
but the feedbacks between them are rarely assessed. Areas with greater
tree diversity tend to be more productive, providing a greater carbon
sink, and biodiversity loss could reduce these natural C sinks. Here, we
quantify how tree and shrub species richness could affect biomass
production at biome, national and regional scales. We find that greenhouse
gas mitigation could help maintain tree diversity and thereby avoid a
9-39% reduction in terrestrial primary productivity across differ biomes,
which cold otherwise occur over the next 50 years. Countries that will
incur the greatest economic damages from climate change stand to benefit
the most from conservation of tree diversity and primary productivity,
which contributes to climate change mitigation. Our results emphasize an
opportunity for a triple win for climate, biodiversity and society, and
highlight how these co-benefits must be focused by reforestation programs.
Supplementary Data S1: A CSV file for the list of target species.
Supplementary Data S2: A CSV file containing the estimations of the effect
sizes (lnRR) to alleviate the loss of woody plant species
[-log(ΔSRmitigation/ΔSRbaseline)] for terrestrial biomes, based on five
Shared Socioeconomic Pathways (SSPs). Results are provided for ensembled
means across three General Circulation Models (GCMs) and each of them. The
upper and lower 95% confidence intervals (UpperCI and LowerCI) are
provided. The number of coarse grids analyzed for each biome
(NoCoarseGrids) is also included. BiomeIDs are consistent with those used
in the paper. Abbreviations for GCMs: Ensembled,
ensembled result; MIROC, MIROC-ESM-CHEM; HadGEM2,
HadGEM2-ES; GFDL, GFDL-CM3. Supplementary Data S3: A CSV
file containing the estimations of the effect sizes (lnRR) of tree
diversity-dependent productivity conservation
[-log(ΔPmitigation/ΔPbaseline)] for terrestrial biomes, based on five
SSPs. Results are provided for ensembled means across three GCMs and each
of them. The upper and lower 95% confidence intervals (UpperCI and
LowerCI) are provided. The number of fine grids analyzed for each biome
(NoFineGrids) is also included. BiomeIDs are consistent with those used in
the paper. Abbreviations for GCMs: Ensembled, ensembled
result; MIROC, MIROC-ESM-CHEM; HadGEM2,
HadGEM2-ES; GFDL, GFDL-CM3. Supplementary Data S4:
Raster files containing the estimations of tree diversity-dependent
productivity conservation [-log(ΔPmitigation/ΔPbaseline)] at a spatial
resolution of 30 arcminutes (maps in geographic coordinates of WGS84;
Extended Data Figure S7), which were calculated using five SSPs and three
GCMs. Value of -999 is for infinite values (denominator or numerator is
zero and thus log-ratio cannot be calculated in these grids).
Abbreviations for GCMs: MIROC, MIROC-ESM-CHEM; HadGEM2,
HadGEM2-ES; GFDL, GFDL-CM3. Supplementary Data S5: A CSV
file containing the estimations of the effect sizes (lnRR) of tree
diversity-dependent productivity conservation
[-log(ΔPmitigation/ΔPbaseline)] of the IPBES subregions, based on five
SSPs. Results are provided for ensembled means across three GCMs and each
of them. The number of fine grids analyzed for each subregion
(NoFineGrids) is also included. Abbreviations for
GCMs: Ensembled, ensembled result; MIROC,
MIROC-ESM-CHEM; HadGEM2,
HadGEM2-ES; GFDL, GFDL-CM3. Supplementary Data S6: A CSV
file containing the estimations of the effect sizes (lnRR) of tree
diversity-dependent productivity conservation
[-log(ΔPmitigation/ΔPbaseline)] of countries (ADM0_A3_IS), based on five
SSPs. Results are provided for ensembled means across three GCMs and each
of them. The number of fine grids analyzed for each country (NoFineGrids)
is also included. Abbreviations for GCMs: Ensembled, ensembled
result; MIROC, MIROC-ESM-CHEM; HadGEM2,
HadGEM2-ES; GFDL, GFDL-CM3
Keywords: FOS: Earth and related environmental sciences